PERAN PAWADAHAN NANANG GALUH BANJARBARU DALAM MEMPROMOSIKAN PARIWISATA DI KOTA BANJARBARU - Ni’mah, Imra’atun; Alfisyah, Alfisyah; Ruswinarsih, Sigit (Jurnal Tugas Akhir Mahasiswa Pendidikan Sosiologi, 2024)
Pawadahan Nanang Galuh Banjarbaru is an Indonesian Tourism Ambassador organization in Banjarbaru City, South Kalimantan. They are tasked with promoting and preserving tourism through activities in collaboration with the Department of Youth, Sports, Culture, and Tourism of Banjarbaru City. This research has two objectives: (1) to describe the role of Pawadahan Nanang Galuh Banjarbaru as tourism ambassadors in Banjarbaru City, and (2) to identify internal conflicts within the organization. The research method employed is qualitative, with data collected through participant observation, interviews, and documentation. The research results were analyzed through data reduction, display, and verification. The findings of the research indicate that: (1) Pawadahan Nanang Galuh Banjarbaru promotes tourism in Banjarbaru City through various means, such as visits to other areas, creative activities, and social media publications, effectively increasing the number of tourist visits. (2) Conflicts within the organization, including in Pawadahan Nanang Galuh Banjarbaru, primarily revolve around task allocation and remuneration among members. It is recommended that the public perceive Nanang Galuh as tourism ambassadors within a formal organization with clear structures and responsibilities, rather than just symbolic bearers of offerings. Hopefully, this will enhance their image in the eyes of the public.